The relationship between sedentary lifestyle and intensity of primary dysmenorrhea in adolescent - I Gusti Ayu Wiratni; Sayu Aryantari Putri Thanaya; Ni Wayan Tianing; I Dewa Gede Alit Kamayoga (Physical Therapy Journal of Indonesia, 2024)
Background: The menstrual cycle can be disrupted by changes in hormone production during menstruation, leading to primary dysmenorrhea. Primary dysmenorrhea is caused by excessive contraction of the myometrium due to the concentration of prostaglandins produced by the endometrium and the endorphin hormone. This study aimed to determine whether there is a relationship between a sedentary lifestyle and the intensity of primary dysmenorrhea in high school girls. Methods: The research method used an observational analytic study with a cross-sectional approach. The sampling technique employed purposive sampling. The total number of subjects in this study was 185, with the independent variable being the intensity of primary dysmenorrhea and the dependent variable being a sedentary lifestyle. Data were collected by distributing the International Physical Activity Questionnaire Short Form (IPAQ-SF) short form and checking pain intensity with the Numeric Rating Scale (NRS). Results: In the Spearman rho analysis test, a significant result was obtained with a correlation coefficient value of 0.647, which means the relationship is strong, and a positive value indicates that the relationship between the variables is in one way. Conclusion: There was a relationship between a sedentary lifestyle and the intensity of primary dysmenorrhea in girls of High School.